How important are capital and total factor productivity for economic growth? - Scott L. Baier; Jr. Gerald P. Dwyer; Robert Tamura (Federal Reserve Bank of Atlanta, 2002)
The authors examine the relative importance of the growth of physical and human capital and the growth of total factor productivity (TFP) using newly organized data on 145 countries that span more than one hundred years for twenty-four of these countries. For all countries, only 3 percent of average output growth per worker is associated with TFP growth. This world average masks interesting variations across countries and regions. Of the nine regions, TFP growth accounts for about twenty percent of average output growth in three regions and between ten and zero percent in the other three regions. In three regions, TFP growth is negative on average. The authors use priors from theories to construct estimates of the relative importance of the variances of aggregate input growth and TFP growth for the variance of output growth across countries. Across all countries, variation in aggregate input growth per worker could account for as much as 35 percent of the variance of the growth of output per worker across countries, and variation in TFP growth could account for as much as 87 percent of that variance. Much of the importance of the variance of TFP growth appears to be associated with negative TFP growth.
Keywords: 330; Productivity; Economic development; Capital; Industrial productivity